Taxonomia integrativa de Astyanax lacustris (Lütken, 1875) (Characiformes, Characidae) das bacias do Alto rio Uruguai, Alto e Baixo rio Paraná e Alto rio São Francisco. - Brezinski, Flavia Carolline (2022)
Astyanax presents great species richness and wide geographic distribution, comprising very similar species and with low detailed taxonomic delimitations, which sometimes results in synonyms. In the present work, we aim through the integration of basic and molecular cytogenetic analysis, analysis of mitochondrial DNA sequences and morphometric analysis to recognize the taxonomic status of OTUs “A. altiparanae”, “A. asuncionensis”, “Astyanax jacuhiensis” that were previously synonymized with A. lacustris. Cytogenetic and morphometric analyzes did not corroborate the synonymization, and suggest that, in addition to A. lacustris, the OTUs A. altiparanae, A. asuncionensis and A. jacuhiensis are valid species. Additionally, the analysis of mitochondrial DNA sequences was diagnostic of A. lacustris in relation to the other species. The analysis of different characters proposed by the integrative taxonomy used in the same individuals could provide greater reliability and minimize the underestimation of biodiversity.